New Insights from Middle Islamic Ceramics from Jerash - Lichtenberger, Achim; Peterson, Alex; Polla, Silvia; Raja, Rubina; Springer, Andreas; Stukenbrok, Heiko; Ting, Carmen (Journal of Islamic Archaeology, 2021)
This article presents selected contextualized ceramic finds of the Middle Islamic period from the Northwest Quarter in Jerash, where a settlement of the same period has been investigated over the last years (2011–2016) within the framework of the Danish-German Jerash Northwest Quarter Project. Twenty-four sherds from various vessel types were selected for petrographic analysis, with 17 of these undergoing organic residue analysis as well. We bring together here the results of these analyses and present the sherds in their archaeological contexts together with the new information from the archaeo-scientific analyses. While on the basis of the results we cannot conclude much about specific vessels being assigned certain kinds of foods, we do present wide-ranging results of differing local and imported ceramics as well as a variety of animal and vegetal remains. The results bring to the forefront new knowledge about clay varieties and availability of different kinds of foodstuffs in Middle Islamic Jerash, a topic which is understudied.